The Emergence and Dissemination of Multidrug Resistant Pseudomonas aeruginosa in Lebanon: Current Status and Challenges during the Economic Crisis - Ahmad Ayman Dabbousi; Fouad Dabboussi; Monzer Hamze; Marwan Osman; Issmat I. Kassem (MDPI AG, 2022)
Pseudomonas aeruginosa is a common cause of healthcare-associated infections and chronic airway diseases in non-clinical settings. P. aeruginosa is intrinsically resistant to a variety of antimicrobials and has the ability to acquire resistance to others, causing increasingly recalcitrant infections and elevating public health concerns. We reviewed the literature on multidrug-resistant (MDR) P. aeruginosa isolated from humans (nosocomial and community-associated), animals, and the environment in Lebanon, a country that has been suffering from a surge in antimicrobial resistance (AMR). We identified 24 studies that described the epidemiology and antimicrobial susceptibility profiles of P. aeruginosa. Our analysis showed that the bacterium was predominant in lesions of patients on mechanical ventilation and in burn patients and those with diabetic foot infections and hematological malignancies. We also found that carbapenem resistance in P. aeruginosa isolates in Lebanon involved both enzymatic and non-enzymatic mechanisms but depended predominantly on VIM-2 production (40.7%). Additionally, MDR P. aeruginosa was detected in animals, where a recent study reported the emergence of carbapenemase-producing P. aeruginosa in livestock in Lebanon. Notably, no studies evaluated the contribution of MDR P. aeruginosa in the environment to human infections. Taken together, our findings highlight the need for AMR surveillance programs and a national action plan to combat resistance in Lebanon.